The genus Haplidia Hope in Lebanon (Coleoptera: Scarabaeidae: Melolonthinae: Rhizotrogini) - Montreuil, Olivier; Uliana, Marco; Sehnal, Richard (Zootaxa, 2020)
New data are given for some species of the genus Haplidia Hope, 1837 belonging to Lebanese fauna or recorded from Lebanon. Haplidia petrovitzi Baraud, 1988, and H. chaifensis Kraatz, 1882, are recorded for the first time from Lebanon. Haplidia endroedii Baraud, 1988 and H. baudii Kraatz, 1892, are removed from the Lebanese fauna. After type examination, Haplidia fissa Burmeister, 1855, is recognized as belonging to the genus Medeotrogus Keith, 2001, and the species recorded under this name from Lebanon is described and named Haplidia karlaeschneiderae Sehnal, Montreuil & Uliana, new species. Haplidia villosicollis Kraatz, 1882, is recorded for the first time from Jordan, and H. joannis Baraud, 1988, from Israel. Correctness of the name Haplidia versus Aplidia is also established.